1996
DOI: 10.1016/s1078-5884(96)80046-3
|View full text |Cite
|
Sign up to set email alerts
|

Vein graft stenosis: Incidence and intervention

Abstract: These results uphold the perceived benefits of a GS programme, although the evidence from the non-treated cases in this series reinforces a need for a large, prospective, randomised trial to confirm the case for GS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(17 citation statements)
references
References 18 publications
1
15
1
Order By: Relevance
“…However, the 18-month data with respect to the incidence of vein graft stenoses are different. These results are in line with the findings of the Bristol group, 32 who showed that in a cohort of patients who did not receive treatment for a stenosis or inflow or outflow problems, there was no difference in terms of patency. Mattos et al 33 have also previously concluded that the majority of stenoses stay patent whether treated or not.…”
Section: Discussionsupporting
confidence: 90%
“…However, the 18-month data with respect to the incidence of vein graft stenoses are different. These results are in line with the findings of the Bristol group, 32 who showed that in a cohort of patients who did not receive treatment for a stenosis or inflow or outflow problems, there was no difference in terms of patency. Mattos et al 33 have also previously concluded that the majority of stenoses stay patent whether treated or not.…”
Section: Discussionsupporting
confidence: 90%
“…8 However, one-third of patients will develop a significant stenosis in the SVG, predominantly in the first year after surgery and maintaining patency has generally been difficult for patients with a failing FP bypass graft, especially in occlusion. 2 Recently, endovascular approaches using DCB have been established as secondary intervention strategies for autologous bypass failure. However, the patency is suboptimal less than 30% after one year of follow-up, and unfortunately, SVG FP bypass restenosis or reocclusion has been encountered in daily clinical practice at a substantial frequency.…”
Section: Discussionmentioning
confidence: 99%
“…Although guidelines recommend surgical FP bypass with saphenous vein graft as the first-line therapy for complex FP lesions , 1 substantial incidence of reocclusion following FP bypass with SVG has been reported, and up to one-third of SVG bypass failure may need additional treatment . 2 There are several strategies for secondary intervention to salvage SVG bypass failure, and it is reported DCB usage prevents restenosis and prolongs the time period for re-intervention. 3 However, some studies reported that the clinical results following DCB use did not differ from conventional therapy.…”
mentioning
confidence: 99%
“…Unfortunately, up to 45% of patients seen with critical lower limb ischemia do not possess a usable ipsilateral GSV [9,10] and it has also been shown that a minimal graft diameter of <3.5 mm is a strong independent factor for an event-causing graft stenosis [11]. In the literature 20-30% of venous bypass grafts develop stenoses in the first postoperative year due to myointimal hyperplasia [12,13] (Fig. 1).…”
Section: Femorodistal Reconstructionmentioning
confidence: 99%